Regeneration of Spent Bleaching Earth by Calcination and Its Morphological Enhancement via KOH Impregnation - Nugraheni, Ika Kusuma; Jaya, Jaka Darma; Nuryati, Nuryati; Sunardi, Sunardi; Irawati, Utami; Faiza, Putri Iis; Saputra, Dita Adi (Universitas Gadjah Mada, 2026)
Spent bleaching earth (SBE), a waste generated from palm oil bleaching, contains residual oil and organic matter that block its pore structure and pose environmental disposal concerns. Regeneration of SBE is therefore essential to enable its reutilization. In this study, SBE was regenerated by calcination and further modified via KOH impregnation at concentrations of 1.00, 0.10, and 0.01 M. The regenerated materials were characterized using XRF, SEM, TEM, XRD, and BET surface area analysis. Calcination combined with 0.10 M KOH impregnation increased the surface area from 8.70 to 93.81 m2/g, approaching the value of activated bleaching earth (94.29 m2/g), and significantly altered pore volume and pore size distribution. These findings indicate that calcination restores the basic structure of SBE, while subsequent KOH impregnation enhances its morphological properties, highlighting the potential of regenerated SBE as a low-cost adsorbent or catalyst support.